Comparative Analysis of the Slope Stability Using Slide and Plaxis 2D Software: A Case Study of Tombel Pozzolan Quarry (South-West Cameroon) - Mambou Ngueyep Luc Leroy; Oscar Rodrigue Michel Kenmoe; Hervé Joël Tchognia Nkuissi; Sylvain Lawou Kouayep; Gael Nkenwoum Chebou; André Chéagé Chamgoué; Innoua Mohamadou (Applied and Environmental Soil Science)
The presented study attempted to use coupled finite element numerical (FEM) and analytical limit equilibrium (LEM) procedures to provide comparative graphical charts demonstrating the geometry, the groundwater condition, the safety factor, and the characteristics of the support, which were implemented in the Dangote Pozzolan quarry at Tombel to preventing the slope instability’s occurrence. Field and laboratory work have been carried out to collect and characterize data. The results obtained with the LEM procedure via Slide 2D showed a safety factor of 0.87, indicating an unstable slope compared to a safety factor of 1.0 obtained with the FEM procedure via Plaxis 2D corresponding to a limited equilibrium state of the slope. The characteristics of the support that can be used to stabilize the slopes are geotextile support of 100% strip coverage, a tensile strength of 100 kN/m, an adhesion property of 4 kPa, and a frictional angle of 40°. The geotextile is anchored at the slope surface. After the support has been introduced, and the new safety factor calculated, the support automatically increased the safety factor value from 0.87 to 1.51 by using Slide 2D and from 1.0 to 1.98 by using Plaxis 2D, which is from an unstable state to a very stable state.